1980
DOI: 10.1002/j.1537-2197.1980.tb07744.x
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, Style, and Obturator of Ornithogalum Caudatum (Liliaceae) and Their Function in the Reproductive Process

Abstract: Transmitting tissue in Ornithogalum is divided into three regions corresponding to classical divisions of the gynoecium: stigma, style, and ovary. The stigma differentiates from epidermal cells of the stylar apex. These cells form the stigmal papillae and have dense cytoplasm with abundant ER and lipid bodies. Papillae have walls with small transfer‐ingrowths. At floral receptivity, papillae secrete a small amount of surface exudate. Epidermal cells of the style contain numerous spherosomes and have thin filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
5

Year Published

1982
1982
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 77 publications
4
25
0
5
Order By: Relevance
“…Different kinds of style may be present in the same group, as in the Caesalpinioideae (Owens 1989) and they may not be that different in their basically secretory nature. As for the species studied, the style is solid, filled by a secretory transmitting tissue, which shows a continuity between the stigma and the placentary obturator, similar to that described for Ornithogalum caudatum (Liliaceae) (Tilton & Horner 1980). The different types of stigma can be related to incompatibility mechanisms (Heslop-Harrison 1975).…”
Section: Discussionsupporting
confidence: 63%
“…Different kinds of style may be present in the same group, as in the Caesalpinioideae (Owens 1989) and they may not be that different in their basically secretory nature. As for the species studied, the style is solid, filled by a secretory transmitting tissue, which shows a continuity between the stigma and the placentary obturator, similar to that described for Ornithogalum caudatum (Liliaceae) (Tilton & Horner 1980). The different types of stigma can be related to incompatibility mechanisms (Heslop-Harrison 1975).…”
Section: Discussionsupporting
confidence: 63%
“…et al (1976) reported the absence of lipids from the exudate of Lycopersicon, lipids do occur in minor amounts in Malus (CREST! et al 1980), and are significant components of the stylar exudates of Forsythia (DuMAS 1974(DuMAS , 1977, Ornithogalum (TILTON and HoRNER 1980), Citrus (CIAMPOLINI et al 1981), and of Galinsoga, as reported here.…”
Section: Discussionsupporting
confidence: 61%
“…(1976); CLARKE and KNOX (1978); FERRARI et al (1981); MAscARENHAS and MARMELSTEIN (1981); HrNATA et al (1982) and NrsHio and HrNATA (1982). Many pubblications intervene between the anatomical and molecular ends of the spectrum, and these are reviewed by, or included in, the works of HANF (1935); VASIL and }oHRI (1964); HESLOP-HARRISON and SHIVANNA (1977), TILTON and HoRNER (1980), and HESLOP-HARRISON (1981).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the syncarpy character is highly relevant for group taxonomy in delimiting the subfamilies, so that, considering the new phylogeny of the family (Givnish et al 2007), its detailed (Tilton & Horner 1980). Sajo et al (2004b) cited the presence of this tissue in the placental region, but did not describe it.…”
Section: Discussionmentioning
confidence: 99%